CELL VIABILITY ASSAY OF FICUS BENGHALENSIS LATEX SOLVENT EXTRACTS ON DIFFERENT CELL LINES - Cdsln, Tulasi; M, Lakshmi Narasu; L, Saida (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Presented here in the study, the screening for antiproliferative activity of Ficus benghalensis dried latex solvent extracts on human breast MDA MB 231, colorectal HCT116, and neuroblastoma IMR 32 cell lines. Methods: The anticancer activity of ethanol, methanol, ethyl acetate, and acetone extracts against the above-mentioned cancer cell lines as well in lymphocytes, by 3-(4,5-Dimethylthiazol-2-Yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay and propidium iodide staining was used to observe the morphological changes occurred in the cell due to the affect of latex extract. Results: Among all the extracts, ethanol extract was found to be effective against IMR 32 and HCT 116 whereas ethyl acetate extract in case of MDA MB 231 cell line with 50% inhibitory concentration 50% (IC50) 123.27±2.5 μg/ml, 99.82±9.06 μg/ml, and 75.66± 6.3, respectively. Conclusion: The extracts were found to be less toxic on peripheral blood lymphocytes. The IC50 value of the cytotoxic activity measured using MTT dye indicated that the extracts were efficient in inhibition of the cell proliferation of these cell lines.